Hamrlick Brewing - ZERRILLO, Philip C. (Institutional Knowledge at Singapore Management University, 2012)
This case is set in April 2011, and begins with Mark Hamrlick considering which of several distribution partners he should choose for his Saxonbräu® beers. Hamrlick is the founder and president of Hamrlick Brewing, a small brewer located in Elmhurst, Illinois. The company began operations just 18 months earlier and has been selling and distributing its product on its own. The company has recently purchased a new state-of the-art bottling machine in hopes to grow sales beyond current levels, which had previously been entirely draft beer (kegs). The company's products, Saxonbräu® Pilsner and Saxonbräu® Bock are high quality beers which have won a number of national awards and received critical acclaim from several beer aficionados. The beer is brewed in accordance with the Reinheitsgebot (German brewing and purity law of 1516) and given its name; is often misperceived as an imported beer. However, sales have been flat and Hamrlick must find a way to grow his young company.